INSTAGRAM AS A LEARNING TOOL: TRENDS AND BENEFITS FOR ENGLISH LANGUAGE STUDENTS' SKILLS - Cahyani, Elvina Dwi; Maghfiroh, Ana (Academic Journal Perspective: Education, Language, and Literature, 2025)
In recent years, Instagram has become a popular platform that supports informal English language learning. This study examines how English language education students use Instagram as a tool to improve their language skills. Using a qualitative descriptive method, data were collected through semi-structured interviews with fourth-semester students at Muhammadiyah University of Ponorogo. Thematic analysis revealed that Instagram enhances vocabulary, grammar, listening, and speaking skills. Features like Reels help improve listening and pronunciation skills, while text and comments support grammar and vocabulary development. Students also reported increased motivation due to Instagram's flexible and relevant learning environment. Despite potential distractions, they adopted strategies such as content filtering and goal-setting. This study contributes to a better understanding of how digital platforms like Instagram can be used to support self-directed language learning and motivation among students. These findings offer valuable insights for educators in designing informal learning activities integrated with technology that align with students' digital habits. Further research is needed through qualitative or quantitative approaches to explore in greater depth the effectiveness of Instagram in enhancing language learning outcomes and validating its role in English language education.